Dealloying electrode catalyst

JP2026536459APending Publication Date: 2026-10-30JOHNSON MATTHEY HYDROGEN TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026513202
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-11
Filing Date
2024-09-25
Publication Date
2026-10-30

Smart Images

  • Figure 2026536459000001_ABST
    Figure 2026536459000001_ABST
Patent Text Reader

Abstract

The present invention provides a process for preparing solid nonporous dealloyed electrode catalyst particles, the process comprising: providing solid nonporous platinum group metal alloy precursor particles PMn, wherein P is a platinum group metal and M is at least one alloying metal; and a dealloying step for providing solid nonporous dealloyed electrode catalyst particles, wherein carbon monoxide is supplied to the precursor particles under conditions that remove at least a portion of the metal M from the surface of the precursor particles, the process comprising: particles of a platinum group metal alloy PMX, wherein P is a platinum group metal and M is at least one alloying metal, the total atomic composition of M relative to P on the surface of the dealloyed electrode catalyst is lower than the total atomic composition of M relative to P in the bulk of the dealloyed electrode catalyst, and x is less than n.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to dealloying electrode catalysts and methods for preparing them. In particular, the electrode catalysts may be suitable for use in fuel cells or electrolytic cells, and the method is a gas-phase method. [Background technology]

[0002] A fuel cell is an electrochemical cell containing two electrodes separated by an electrolyte. A fuel, such as hydrogen, an alcohol like methanol or ethanol, or formic acid, is supplied to the anode, and an oxidizer, such as oxygen or air, is supplied to the cathode. An electrochemical reaction occurs at the electrodes, converting the chemical energy of the fuel and oxidizer into electrical energy and heat. Electrode catalysts are used to facilitate the electrochemical oxidation of the fuel at the anode and the electrochemical reduction of oxygen at the cathode.

[0003] Fuel cells are typically classified according to the properties of the electrolyte used. In many cases, the electrolyte is a solid polymer membrane, which is electronically insulating but ionically conductive. In a proton exchange membrane fuel cell (PEMFC), the ionically conductive membrane is proton conductive, and protons generated at the anode are transported across the ionically conductive membrane to the cathode, where they combine with oxygen to form water.

[0004] The main component of a PEMFC is a membrane electrode assembly consisting of five layers. The central layer is a polymer ion-conducting membrane. On both sides of the ion-conducting membrane are electrocatalyst layers containing electrocatalysts designed for specific electrolytic reactions. Finally, adjacent to each electrocatalyst layer is a gas diffusion layer. The gas diffusion layer must allow reactants to reach the electrocatalyst layers and conduct the current generated by the electrochemical reaction. Therefore, the gas diffusion layer must be porous and conductive.

[0005] Electrocatalytic catalyst layers generally contain electrocatalytic catalyst materials, including metals or metal alloys suitable for fuel oxidation or oxygen reduction reactions, depending on whether the layer is used as an anode or cathode. Electrocatalysts for fuel oxidation and oxygen reduction are typically based on platinum or platinum alloyed with one or more other metals. It is known that the activity of platinum alloy electrode catalysts can be increased by a dealloying process, which selectively removes the alloying metal from the electrode catalyst surface to provide a platinum-rich surface. This is conventionally carried out by an acid leaching process. It is desirable to provide a process for preparing dealloyed electrode catalysts suitable for industrial applications, which are safe, reliable, and consistently produce high-performance electrode catalysts. [Overview of the project]

[0006] The inventors have conveniently found that solid, non-porous dealloyed electrode catalyst particles can be provided by using gaseous carbon monoxide in the dealloying process. This has the advantage of not requiring acidic solutions, which are difficult to control in industrial environments. Surprisingly, the electrode catalyst particles prepared by this process have higher mass activity than those prepared by conventional acid-based leaching methods. In addition, compared to liquid acid-based methods, the gas can be more easily accessed by all the particles in the powder, thus achieving more uniform dealloying of the particle powder sample.

[0007] Therefore, this disclosure provides a process for preparing solid non-porous dealloying electrode catalyst particles, the process is Solid nonporous platinum group metal alloy precursor particles PM n A process of providing a formula in which P is a platinum group metal and M is at least one alloying metal, A dealloying process for providing solid, non-porous dealloying electrode catalyst particles includes the step of supplying carbon monoxide to precursor particles under conditions that remove at least a portion of the metal M from the surface of the precursor particles, Dealloying electrode catalyst particles are platinum group metal alloy PM xThe particles are such that P is a platinum group metal, M is at least one alloying metal, the total atomic composition of M relative to P on the surface of the dealloyed electrode catalyst is lower than the total atomic composition of M relative to P in the bulk of the dealloyed electrode catalyst, and x is less than n.

[0008] The Disclosure also provides dealloyed electrode catalyst particles obtainable by the process of the Disclosure. In particular, the electrode catalyst particles are oxygen reduction reaction electrode catalyst particles. The Disclosure also provides a catalyst layer comprising electrode catalyst particles. Additionally, the Disclosure provides a catalyst coating film for a fuel cell or water electrolytic cell comprising a gas diffusion electrode having a catalyst layer and a gas diffusion layer, and an ion-conducting film having a cathode catalyst layer applied to a first surface of the film and / or an anode catalyst layer applied to a second surface of the film, wherein the cathode catalyst layer is the catalyst layer according to the Disclosure.

[0009] Also provided are membrane electrode assemblies for fuel cells or water electrolytic cells, comprising a catalyst coating film according to the disclosure and at least one of a gas diffusion layer or a porous transport layer, or a gas diffusion electrode according to the disclosure and an ion-conducting film. Additionally, a water electrolytic cell or fuel cell comprising a catalyst coating film according to the disclosure or a membrane electrode assemblies according to the disclosure. [Brief explanation of the drawing]

[0010] [Figure 1] This is a transmission electron microscope (TEM) line scan of a dealloyed electrode catalyst prepared by the process of the present invention. [Figure 2] This is a TEM scan of another dealloying electrode catalyst prepared by the process of the present invention. [Figure 3] This chart provides mass activity data for the electrode catalysts prepared by the process of the present invention, along with a reference electrode catalyst. [Modes for carrying out the invention]

[0011] The dealloyed electrode catalyst particles prepared in this disclosure are solid and non-porous. That is, they are not nanoframes or hollow nanostructures and do not contain a network of pores interconnected throughout the catalyst particle. The dealloyed electrode catalyst particles contain a solid volume extending from the center of the particle to a radial point from which at least some of the metal M has been removed. Whether the electrode catalyst particles are solid and non-porous can be confirmed, for example, by analyzing linear scanning transmission electron microscopy data obtained by a process such as the protocol discussed herein. For example, when looking at PtNi dealloyed electrode catalyst particles, the fact that the particles are solid and non-porous is confirmed by the presence of a continuous metal trace across the particle. If the particles are, for example, nanoframes having a network of pores interconnected throughout the particle, there is no continuous metal trace across the particle. The precursor particles and dealloyed electrode catalyst particles may preferably have a particle size of about 15 nm or less, preferably about 10 nm or less, for example about 5 nm or less, which is a number-average particle size determined by transmission electron microscopy analysis. The precursor particles and dealloyed electrode catalyst particles may preferably have a particle size of at least about 2 nm. Electrocatalyst particles within this particle size range are particularly suitable as electrode catalysts for oxygen evolution reactions and are typically selective for other reactions, such as hydrogen evolution reactions, where such reactions may occur.

[0012] P is a single platinum group metal, namely ruthenium, rhodium, palladium, osmium, iridium, or platinum. Preferably, P is selected from ruthenium, rhodium, palladium, and platinum, and is typically platinum and palladium. Most preferably, P is platinum.

[0013] M is preferably at least one base metal, typically two or fewer base metals (i.e., ternary and binary alloys), and most typically it is one base metal (i.e., a binary alloy). The base metal is tin or a transition metal that is not a noble metal. Suitable base metals include copper, cobalt, nickel, zinc, iron, titanium, molybdenum, vanadium, manganese, niobium, tantalum, chromium, and tin. More preferably, the base metal is selected from nickel, copper, cobalt, and chromium. Most preferably, the base metal is nickel.

[0014] The dealloying process reduces the amount of metal M in the particles. Metal M is removed from the surface of the particles to the radial point where the solid volume begins. Therefore, x is less than n. The value of n is preferably 1 or greater, more preferably 1.5 or greater, and typically 2.0 or greater. The value of n is typically 5 or less. The value of x is preferably less than 1, more preferably 0.7 or less, and more preferably 0.5 or less. The value of x may preferably be 0.1 or greater. The fact that the dealloyed particles have a total atomic composition of M relative to P on the surface of the dealloyed electrode catalyst that is lower than the total atomic composition of M relative to P in the bulk of the dealloyed electrode catalyst can be confirmed, for example, by analyzing linear scanning transmission electron microscopy data obtained by a process such as the protocol discussed herein. "Bulk" means the entire electrode catalyst particle. For example, when examining PtNi alloy electrode catalyst particles, the fact that the particles are such dealloyed particles is confirmed by the fact that the platinum trace begins to rise in the count, followed by the nickel trace, and / or the traces rise at different rates as they continue across the particle. This can be seen in Figures 1 and 2, including the circled area in Figure 2. Dealloyed electrode catalyst particles PtNi x The total atomic composition of M relative to P on the surface of the dealloyed electrode catalyst may be 20-99%, preferably 30-99%, lower than the total atomic composition of M relative to P in the bulk of the dealloyed electrode catalyst. "20-99% lower" means:

[0015]

number

[0016] Precursor particles, and therefore dealloyed electrocatalysts, may also be supported or unsupported, typically on a conductive support. "Supported" takes on its conventional definition in the art. For example, the term "supported" will be understood to include electrocatalysts dispersed on a support material and bonded or immobilized to the support material by physical or chemical bonds. For example, an electrocatalyst may be bonded or immobilized to the support material by ionic or covalent bonds, or by nonspecific interactions such as van der Waals forces. The support itself is typically in particulate form. The support may be a conductive carbon support material. Preferably, the conductive carbon support material is carbon powder, which may be, for example, carbon black or graphitized carbon black, e.g., commercially available carbon black (Cabot Corp. (Vulcan® XC72R) or Akzo Nobel (Ketjen® Black Series)). Another suitable carbon support material is acetylene black (e.g., available from Chevron Phillips (Shawinigan Black®) or Denka).

[0017] Precursor particles can be prepared by any conventional technique. For example, a method similar to the general method for preparing carbon-supported catalysts described in International Publication No. WO2013 / 045894 can be used. For example, first, a dispersion of a pre-formed platinum group metal catalyst, e.g., Pt / C, is prepared in a suitable solvent, e.g., water, and to this, a salt of metal M dissolved in a suitable solvent, e.g., water, is added together with a base in appropriate mixing. Once the deposition of metal M on the Pt / C catalyst is complete, the formed material is isolated, dried, and annealed, e.g., by filtration.

[0018] The dealloying step is carried out by supplying carbon monoxide to the precursor particles under conditions that remove at least a portion of the alloying metal M from the surface of the precursor particles. As will be apparent to those skilled in the art, the process is analogous to the Mondo process, which extracts nickel by exposure to carbon monoxide acting as both a reducing agent and a complexing agent, and removes nickel as a complex such as Ni(CO)4. In the process of the present invention, carbon monoxide is typically supplied in gaseous form. Inert gases such as nitrogen may also be present, but the gas to which the precursor particles are exposed is primarily carbon monoxide, typically more than about 99% of the total volume, for example, about 100% of the total volume. The temperature to which the precursor particles are exposed to carbon monoxide is typically elevated, i.e., higher than the ambient temperature (about 25°C). This can be achieved, for example, by exposing the precursor particles to carbon monoxide in a furnace such as an electric heating furnace, or by flowing carbon monoxide through the furnace. The precursor particles can preferably be exposed to carbon monoxide at a temperature of at least about 100°C, and preferably at least about 150°C. Precursor particles can preferably be exposed to carbon monoxide at temperatures up to about 300°C, preferably up to about 250°C. Such a range is advantageous in balancing the effectiveness of the dealloying process with not damaging the catalyst. The duration of exposure of precursor particles to carbon monoxide depends on the properties and quantity of the particles. Those skilled in the art can determine when to terminate the exposure by monitoring the nickel carbonyl content in the gaseous emissions, which can be measured, for example, by chemical absorption and nickel analysis by ICP-OES. Generally, a suitable duration of exposure to carbon monoxide is about 24 hours or less, preferably about 12 hours or less, for example, about 5 hours or less. A suitable duration is typically at least about 0.25 hours. The process can be carried out at ambient pressure, but high pressure can allow the use of lower temperatures and faster process times. Precursor particles can be exposed to carbon monoxide at pressures of about 50 bara or less, preferably about 30 bara or less, preferably about 15 bara or less, for example, about 5 bara or less. Precursor particles can typically be exposed to carbon monoxide at a pressure of approximately 1 bara or higher.Carbon monoxide can typically be supplied at a gas hourly space velocity (GHSV) of about 5000 Nl / l / hr or less, preferably about 3000 Nl / l / hr or less, preferably about 2000 Nl / l / hr or less. Carbon monoxide can typically be supplied at a GHSV of at least about 500 Nl / l / hr. The dealloying step can additionally include a separate step of bringing the precursor particles into contact with an acidic solution, either before or after, typically after, supplying carbon monoxide, to remove a portion of the alloying metal from the surfaces of the precursor particles. However, the dealloying step may preferably not include the step of bringing the precursor particles into contact with an acidic solution.

[0019] Carbon monoxide can be supplied to the precursor particles in a closed-loop process in which metal M can be removed from the process by chemical vapor transport. The closed-loop process can include monitoring the transport of volatile metal carbonyl species such that the species decompose and metal M is deposited at a decomposition site remote from the precursor particles. In other words, the deposition rate and total amount of pure nickel deposited in the decomposition zone can be monitored by at least one of various well-known methods for determining the completion of the dealloying process, for example, by nickel analysis via chemisorption and ICP-OES. At such decomposition sites, the metal is sequestered from the metal complex, for example Ni(CO)₄, so that the metal can be effectively transported away from the process, while carbon monoxide can re-enter the process for maximum efficiency. The metal can be sequestered by any suitable conditions, for example, reduction of carbon monoxide pressure, addition of oxygen, or application of heat treatment. The ideal decomposition temperature is below the temperature at which the Boudouard reaction occurs. For example, the volatile metal carbonyl species are exposed at the decomposition site to a temperature of at least about 200°C, preferably at least about 250°C, preferably about 450°C or less. When not at the decomposition site, the gas is preferably maintained at a temperature of less than about 200°C, preferably less than about 180°C.

[0020] The dealloyed electrode catalyst particles prepared by the process are suitable for use as electrode catalysts in fuel cells or electrolytic cells, typically proton exchange membrane fuel cells or electrolytic cells. For example, the electrode catalyst may be an oxygen reduction reaction catalyst typically used in the cathode catalyst layer of a proton exchange membrane fuel cell. Accordingly, this disclosure also provides dealloyed electrode catalysts, preferably dealloyed oxygen evolution reaction electrode catalysts, that can, preferably, be obtained by the process disclosed herein.

[0021] The dealloyed electrode catalyst prepared by the process of the present invention can be incorporated into a catalyst coating film for a fuel cell or water electrolytic cell, typically the cathode catalyst layer being obtainable by the process disclosed herein, preferably for a proton exchange membrane fuel cell, which includes the dealloyed electrode catalyst obtained thereby, and comprising an ion-conducting membrane having a cathode catalyst layer applied to a first surface of the membrane and / or an anode catalyst layer applied to a second surface of the membrane. To prepare the catalyst layer, the electrode catalyst and any additional components are dispersed in aqueous and / or organic solvents to prepare a catalyst ink. If necessary, particle disruption is performed by methods known in the art, such as high-shear mixing, milling, ball milling, passage through a microfluidizer, or a combination thereof, to achieve a suitable particle size distribution. After the preparation of the catalyst ink, the ink is deposited onto a substrate (e.g., a gas diffusion layer, an ion-conducting membrane, or a support material / transfer substrate) to form the catalyst layer. The ink may be deposited by any suitable technique known in the art, including but not limited to gravure coating, slot die (slot, extrusion) coating, screen printing, rotary screen printing, inkjet printing, spray, paint, bar coating, pad coating, gap coating techniques such as knife or doctor blade overroll, and the application of a measuring rod. In the catalytic coating film, a catalytic coating film is formed by depositing a catalyst layer on an ion-conductive film either by directly coating the film with catalytic ink or by indirectly transferring it from a decal transfer substrate. The catalytic coating film of the present invention may include a second catalyst layer on its opposite side, which may or may not be in accordance with the present invention.The ion-conductive membrane is preferably any membrane suitable for use in proton exchange membrane fuel cells, for example, the membrane may be based on perfluorinated sulfonic acid materials such as Nafion™ (Chemours Company), Aquivion® (Solvay Specialty Polymers), Flemion® (Asahi Glass Group), and Aciplex™ (Asahi Kasei Chemicals Corp.), as well as perfluorosulfonic acid ionomer materials manufactured by 3M®. Alternatively, the membrane may be based on sulfonated hydrocarbon membranes, such as those available from FuMA-Tech GmbH as the fumapem® P, E or K series of products, or those available from JSR Corporation, Toyobo Corporation and others.

[0022] A catalyst layer can be deposited on a gas diffusion layer to form a gas diffusion electrode of the disclosure comprising the catalyst layer and the gas diffusion layer. The gas diffusion layer includes a gas diffusion substrate, preferably a microporous layer. When a microporous layer is present, the catalyst layer is deposited on the microporous layer. Typical gas diffusion substrates include nonwoven paper or webs containing a network of carbon fibers and a thermosetting resin binder (e.g., TGP-H series carbon fiber paper available from Toray Industries Inc. (Japan), H2315 available from Freudenberg FCCT KG (Germany), Sigracet® series available from SGL Technologies GmbH (Germany), or Ballard Power Systems Examples include the AvCarb® series or carbon woven fabrics manufactured by Inc. Carbon paper, web, or cloth may be pretreated before electrode manufacturing to make it either more wettable (hydrophilic) or more wettable (hydrophobic) and incorporated into membrane electrode assemblies. The nature of any treatment depends on the type of fuel cell or water electrolyzer and the operating conditions under which it is used. Substrates can be made more wettable by incorporating materials such as amorphous carbon black through impregnation from a liquid suspension, or they can be made more hydrophobic by impregnating the pore structure of the substrate with a colloidal suspension of a polymer such as PTFE or polyfluoroethylene propylene (FEP), followed by drying and heating above the softening point of the polymer. Typical microporous layers include mixtures of carbon black and polymers such as polytetrafluoroethylene (PTFE).

[0023] Furthermore, a membrane electrode assembly for a fuel cell or water electrolytic cell is also provided, comprising a catalyst coating film according to the disclosure and at least one of a gas diffusion layer or a porous transport layer, or a gas diffusion electrode according to the disclosure and an ion-conducting film. Also provided are a water electrolytic cell or fuel cell, preferably a proton exchange membrane fuel cell or electrolytic cell, comprising the catalyst coating film or the membrane electrode assembly disclosed herein. [Examples]

[0024] Comparative Example Comparative Example 1 was prepared using a method similar to the general method for preparing carbon-supported catalysts described in International Publication No. WO2013 / 045894, and then annealed.

[0025] To prepare Comparative Examples 2 and 3, 1 kg of particulate carbon black-supported platinum (30 w% Pt / C, 300 g Pt, 1.538 mol) catalyst material precursor was prepared using a method similar to the general method for preparing carbon-supported catalysts described in International Publication No. WO2013 / 045894. This precursor was dispersed in 75.7 L of water in a reaction vessel. Solid NaHCO3 (577 g, 6.869 mol) was added. Subsequently, a 6.1 L solution of nickel nitrate (907.1 g Ni(NO3)2.6H2O, 183 g Ni, 3.11 mol) in desalinated water was added. When nickel deposition was complete, the catalyst was recovered by filtration and washed on a filter bed with desalinated water until no soluble ions remained. The material was dried and annealed.

[0026] 942g of alloyed PtNi2 / C was slurryed in 18L of 0.5M H2SO4, heated at 80°C for 24 hours, filtered, washed on a filter bed with demineralized water until all soluble ions were removed, and then dried to provide 822g of Comparative Example 2.

[0027] Next, 260g of Comparative Example 2 was re-slurried in a mixture of 4L of 0.625M H2SO4 and 1L of n-propanol, heated at 80°C for 24 hours, filtered, washed on a filter bed with demineralized water until all soluble ions were removed, and then dried to provide 251g of Comparative Example 3.

[0028] Examples of the Invention To prepare Example 1, 11.9 g of Comparative Example 2 was added to a 3 / 4” stainless steel reactor. The reactor was placed in an electric heating furnace with temperature measurement: furnace heater, reactor wall, and process. The reactor was connected to a gas supply line capable of supplying hydrogen, nitrogen, and carbon monoxide by a mass flow controller. The pressure was controlled by a manually set gas pressure regulator. Nitrogen was introduced at 2000 Nl / l / hr GHSV at ambient pressure to sweep the oxygen component. Then hydrogen was introduced at 2000 Nl / l / hr GHSV, and the reactor was heated to 180°C and held for 30 minutes. Then the reactor was swept with nitrogen, the pressure was increased to 30 barg, and the process temperature was increased to 160°C. The nitrogen flow was stopped, and then carbon monoxide was introduced at 3000 Nl / l / hr GHSV. Once carbon monoxide was detected at the reactor outlet, the test was initiated, and the product was in contact with carbon monoxide for 105 minutes. The vent gas from the reactor was passed through an absorption column to extract the nickel carbonyl formed in the reactor, and nickel analysis was performed by ICP-OES. Nickel analysis performed on the absorption column liquid was measured at 102,000 micrograms / liter. After 105 minutes, the carbon monoxide flow was stopped, and nitrogen was introduced into the reactor at 2000 Nl / l / hr GHSV. The reactor was cooled to ambient temperature, and the pressure was reduced to ambient. The product was then released onto carbon dioxide and recovered after the carbon dioxide evaporated.

[0029] To prepare Example 2, 12.71 g of PtNi2 / C material, prepared by a procedure similar to that used to prepare Comparative Example 1, was added to a 3 / 4” stainless steel reactor. The reactor was placed in an electric heating furnace, with temperature measurement, furnace heater, reactor wall, and process. The reactor was connected to a gas supply line capable of supplying hydrogen, nitrogen, and carbon monoxide by a mass flow controller. Pressure was controlled by a manually set gas regulator. Nitrogen was introduced at 2000 Nl / l / hr GHSV at ambient pressure to sweep the oxygen component. Hydrogen was then introduced at 2000 Nl / l / hr GHSV, and the reactor was heated to 180°C and held for 30 minutes. The reactor was then swept with nitrogen, and the pressure was increased to 30 barg. The process temperature was increased to 214°C. The nitrogen flow was stopped, and then carbon monoxide was introduced at 1000 Nl / l / hr GHsV. When carbon monoxide was detected at the reactor outlet, the test was initiated, and the product was in contact with carbon monoxide for 199 minutes. The vent gas from the reactor was passed through an absorption column to extract the nickel carbonyl formed in the reactor, and nickel analysis was performed by ICP-OES. Nickel analysis performed on the absorption column liquid was measured at 934,000 micrograms / liter. After 199 minutes, the carbon monoxide flow was stopped, and nitrogen was introduced into the reactor at 2000 NL / l / hr GHsV. The reactor was cooled to ambient temperature, and the pressure was reduced to ambient. The product was then released onto carbon dioxide and recovered after the carbon dioxide evaporated.

[0030] Transmission electron microscopy (TEM) analysis To acquire TEM data, the sample was pulverized between two glass slides and dusted onto a Holley carbon-coated Cu TEM grid. The sample was examined using a JEM2800 (scanning) transmission electron microscope under the following instrument conditions: voltage (kV) 200, C2 aperture (µm) 70 and 40, and dark-field (Z contrast) imaging in scanning mode with an off-axis annular detector. SE signals were acquired simultaneously with other STEM images providing topological information of the sample. Compositional analysis was performed by X-ray emission detection in scanning mode.

[0031] Figures 1 and 2 show both that the dealloyed electrode catalyst particles prepared above are solid and that their surface is primarily platinum-containing. The blue traces indicate the platinum concentration when scanning across the three particles shown in the TEM image. The red traces indicate the nickel concentration when scanning across the three particles shown in the TEM image. The fact that the surface is primarily platinum-containing is evident from the fact that the nickel trace begins to increase in count after the platinum trace begins to increase in count, and that the traces increase at different rates as the traces continue across the particles. The fact that the electrode catalyst particles are solid and not, for example, nanoframes is evident from the continuous traces for both metals.

[0032] mass activity By depositing the anode and cathode catalyst layers onto a PTFE sheet and transferring the appropriate layer to either side of a perfluorosulfonic acid (PFSA) reinforced film (15 μm thick) at a temperature of 150°C to 200°C, a 50 cm² layer is created. 2 A catalyst-coated membrane (CCM) was prepared for the active region of the material. A gas diffusion layer was applied to each surface of each CCM to form a complete membrane electrode assembly (MEA). The gas diffusion layer used was carbon fiber paper having a hydrophobic microporous layer containing carbon and PTFE applied to the surface in contact with the CCM.

[0033] To measure the electrocatalytic mass activity, the MEA was set to 170 kPa. ゲージ-入口 , 100% RH, and 500 mA cm under H2 / air conditions at 80°C -2 The voltage was adjusted by applying a constant current density. The battery voltage was monitored until a stable value was observed. Subsequently, the cathode catalyst layer was exposed to a series of cathode depletion processes, and then 500 mA cm was applied until a stable voltage was observed. -2 The current was maintained for 2 hours.

[0034] The catalyst dynamic mass activity was measured using fully humidified and pressurized anode and cathode (100% RH, 50 kPa ゲージ-入口 ) conditions at 80°C, using pure hydrogen and oxygen as the anode and cathode reactants respectively, on a 50 cm 2 MEA. An oxygen polarization curve with current density hold from 0.05 to 0.5 A cm -2 was performed, the current density was maintained for 3 minutes at each step, and the voltage was recorded at the end of the hold. The electrocatalyst mass activity value at 0.9 V was obtained from the ascending polarization curve by extrapolation of the resistance-corrected (iR-corrected) current and normalization by the mass of platinum in the cathode catalyst layer.

[0035] Figure 3 illustrates that the electrocatalyst particles of Example 2 have much higher mass activity than Comparative Example 1. The electrocatalyst particles also have higher activity than Comparative Example 2, in which dealloyed electrocatalyst particles were prepared using conventional acid leaching techniques.

Claims

1. A process for preparing solid non-porous dealloying electrode catalyst particles, wherein the process comprises: Solid nonporous platinum group metal alloy precursor particles PM n A process of providing a formula in which P is a platinum group metal and M is at least one alloying metal, A dealloying step for providing the solid non-porous dealloying electrode catalyst particles includes a step of supplying carbon monoxide to the precursor particles under conditions that remove at least a portion of the metal M from the surface of the precursor particles, The dealloying electrode catalyst particles are platinum group metal alloy PM x A process in which particles are, in the formula, P is a platinum group metal, M is at least one alloying metal, the total atomic composition of M with respect to P on the surface of the dealloying electrode catalyst is lower than the total atomic composition of M with respect to P in the bulk of the dealloying electrode catalyst, and x is less than n.

2. The process according to claim 1, wherein P is platinum.

3. The process according to claim 1, wherein M is a single alloying metal, preferably nickel.

4. The process according to any one of claims 1 to 3, wherein the dealloying electrode catalyst particles are supported.

5. The process according to any one of claims 1 to 4, wherein the dealloying electrode catalyst particles have a particle size of about 15 nm or less.

6. The process according to any one of claims 1 to 5, wherein the carbon monoxide is supplied in a closed-loop process.

7. The process according to claim 6, comprising monitoring the transport of volatile metal carbonyl species such that the species decomposes and the metal M is deposited at decomposition sites away from the precursor particles.

8. Dealloyed electrode catalyst particles obtainable by the process described in any one of claims 1 to 7.

9. The dealloying electrode catalyst particle according to claim 8, which is an oxygen reduction reaction electrode catalyst particle.

10. A catalyst layer comprising the electrode catalyst particles described in claim 8 or 9.

11. A gas diffusion electrode comprising a catalyst layer according to claim 10 and a gas diffusion layer.

12. A catalyst coating film for a fuel cell or water electrolytic cell, wherein the catalyst coating film comprises an ion-conducting film having a cathode catalyst layer applied to a first surface of the film and / or an anode catalyst layer applied to a second surface of the film, and the cathode catalyst layer is the catalyst layer described in claim 10.

13. A membrane electrode assembly for a fuel cell or water electrolytic cell, comprising a catalyst coating film according to claim 12 and at least one of a gas diffusion layer or a porous transport layer, or a gas diffusion electrode according to claim 10 and an ion conductive film.

14. A water electrolytic cell or fuel cell comprising a catalyst coating film according to claim 12, or a film electrode assembly according to claim 13.